Foundation stone - Warren, Lella (University, Ala. : University of Alabama Press, 1986)
Using the history of Alabama and the stories of her pioneering ancestors, Lella Warren created the Whetstone clan who settled Alabama in the 1820s, helped lead it into the prosperity of the 1850s, and fought for it in the War Between the States. The historical background of Foundation Stone is authentic, but, more, it is a compelling story about believable characters. The story of these people-three generations of Whetstones-captures the American pioneering spirit. As an unidentified reviewer described the novel, "Lella Warren's 'Foundation Stone' is the long, well-told chronicle of a family
Introduction by Nancy G. Anderson; Book One: The Home Place; Book Two: Pioneering; Book Three: The Land Yields; Book Four: The Cotton Snobs; Book Five: Cotton Militant; Book Six: The Land Scarred; Book Seven: Rock Wall
Includes bibliographical references (pages xxxiii-xxxiv).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Women authors, American -- Alabama; Women authors, American -- Southern States; Écrivaines américaines -- Alabama; Écrivaines américaines -- États-Unis (Sud); Women authors, American; Alabama; Southern States; Fiction; Historical fiction; Fiction; Romans